Employers' liability for occupational stress and death from overwork (karoshi) of workers in Japan. (14th November 2008) - Kobayashi, Tamie; Middlemiss, Sam
In this paper, we will undertake analysis of the legal treatment of stress related illness at work and death by overwork (known as karoshi) in Japan. We will endeavour to explain the severity of the problem of stress related illness and death by overwork (including death by suicide) in Japan and how its judiciary and government have provided protection and/or redress to its victims or their executors. How the law deals with this problem in Japan will be considered in detail and lessons taken from this to assist in dealing with the growing problem in the USA and the UK.